Projektowanie mierników w zarządzaniu dokonaniami przedsiębiorstwa - Nita, Bartłomiej (Measures Design in Corporate Performance Management, 2008)
The aim of the paper is to explore the process of designing performance measures. The author tries to answer the question: „what elements should a well-designed performance measurement system consist of?” Thus the methodological framework for designing a comprehensive performance measurement system was proposed. This framework was derived from the extensive literature studies and recommendations of various proponents as well as from the author’s own experience.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 306-324